Just Pain: Aquinas on the Necessity of Retribution and the Nature of Obligation - Diem, William Matthew (American catholic philosophical quarterly, 2022)
Although it is common in the Catholic moral tradition to hear punishment spoken of as "just" and demanded by reason, it is remarkably difficult to say why reason demands that malefactors suffer or to articulate what is rendered to whom in punishment. The present essay seeks to fill this lacuna by examining Aquinas's treatment of punishment. After examining several themes found in his work, the paper will conclude that the conceptual key to the reasonableness of punishment is to be found in the norm that demands contrapassum and that this norm is immediately derived from the same moral insight as the Golden Rule. Thus, the paper concludes, the notion of retribution is intimately and inextricably bound up in insights that are foundational to any coherent Christian ethics.